Assessing the operating temperature of multi-junction solar cells with novel rear side layer stack and local electrical contacts - Alonso,Alvarez D; Weiss,C; Fernandez,J; Janz,S; Ekins-Daukes,N (Solar Energy Materials and Solar Cells, 2019)
Sub-bandgap sunlight provides a source of heat generation in solar cells that is detrimental to performance, especially in space applications where heat dissipation is limited. In this work we assess the impact that an advanced rear-side contact scheme for multi-junction solar cells has on the cell temperature. Our results show that this scheme reduces the optical power absorption below the bandgap of germanium by 81% compared to a standard, full metallization design. Measurements of the electrical and thermal power fluxes performed in vacuum demonstrate that this lower near-infrared light absorption results in 8% less heat dissipated in the cell with the novel rear-side contact scheme when operating at 25 ºC. Modelling of the operating temperature for both cells when fully encapsulated with glass indicates that this effect will also result in a reduction of the operating temperature of 9 ºC for the novel design.